Pituitary Apoplexy After Intravitreal Injection of Vascular Endothelial Growth Factor Inhibitor: A Novel Complication - Kasl, Rebecca A.; Kistka, Heather M.; Turner, Justin H.; Devin, Jessica K.; Chambless, Lola B. (Journal of Neurological Surgery Reports, 2015)
Pituitary adenomas are common in the general population. They can be complicated by intratumoral hemorrhage, otherwise known as apoplexy, which frequently presents with neurologic deficits that may necessitate urgent surgical decompression. Many risk factors for pituitary apoplexy have been suggested in the literature. We present a case of symptomatic apoplexy in a woman following the intravitreal administration of the vascular endothelial growth factor (VEGF) inhibitor ranibizumab. Ophthalmoplegia resolved and visual acuity significantly improved following gross total resection of the tumor via an endoscopic endonasal surgical approach. The association between intravitreal injection of a VEGF inhibitor and pituitary apoplexy has not been previously described, but physicians performing these procedures should be aware of this potential complication.
Keywords: pituitary apoplexy; hemorrhage; vascular endothelial growth factor inhibitor; ranibizumab